Cartilage "Clew" Lesion: Report of a Severe Case of Cam-Type Hip Impingement after Slipped Capital Femoral Epiphysis - Hinzpeter, Jaime; Zamorano, Álvaro; Barrientos, Cristian; Barahona, Maximiliano; Robles, Guillermo (Highlights on Medicine and Medical Science Vol. 7, 2021)
This case report aims to describe a severe case of cam-type hip impingement after slipped capital femoral epiphysis (SCFE) in which a periosteal sleeve rolled upon itself, forming a clew of cartilage, was found in the hip arthroscopy. This reinforces the severity and relations of SCFE and hip impingement, leading to functional impairment and early onset of osteoarthritis in a 16-year-old female patient. The cartilage clew lesion was characterized by a total thickness detachment of an extensive area of femoral cartilage, which has the appearance of a large flap of cartilage that folded in on itself. We think that the slipped epiphysis was of such magnitude that the movements of abduction/flexion and internal rotation produced a fracture on the subchondral bone of the femoral head. The perpetuation of the mechanical problem caused a detachment of the femoral cartilage that led to creating an extended flap that began to fold up to itself. Despite hip arthroscopy successfully managing the hip pain in this patient at one-year follow-up, the probability of a hip replacement in the near future for this young woman is still high, which reminds the importance of diagnosis and treatment SCFE.